Corrosion behavior of AA2055 aluminum-lithium alloys anodized in the presence of sulfuric acid solution - Samaniego Gámez, Pedro Oliver; Almeraya Calderón, Facundo; Maldonado Bandala, Erick; Cabral Miramontes, José Ángel; Nieves Mendoza, Demetrio; Olguín Coca, Javier; López León, Luis Daimir; Silva Vidaurri, Luis Gerardo; Zambrano Robledo, Patricia del Carmen; Gaona Tiburcio, Citlalli (Molecular Diversity Preservation International, 2021)
The aim of this work was to evaluate the corrosion behavior of the AA2055 Aluminum-lithium alloy anodized in a sulfuric acid (H2SO4) bath, varying the current density of 0.19 and 1 A·cm−2 and why the sealing solution was water (H2O) and sodium dichromate (Na2Cr2O7). Anodized samples were exposed to a 10 vol.% H2SO4 solution and the electrochemical technique used was electrochemical impedance spectroscopy. Scanning electron microscopy and X-ray photoelectron spectroscopy were employed to characterization of the anodizing layer, determinate morphology and thickness of coatings. The Na2Cr2O7 sealing solution tends to increase the charge transfer resistance and produces a more homogeneous and compact passive oxide layer, and imparts a corrosion inhibition protection to the AA2055. SEM observations indicated that the morphology and thickness of the anodic films formed on AA2055 aluminum-lithium alloy anodized have the best results for both current densities.